2005
DOI: 10.1016/j.febslet.2005.11.078
|View full text |Cite
|
Sign up to set email alerts
|

FCH/Cdc15 domain determines distinct subcellular localization of NOSTRIN

Abstract: NOSTRIN, an NO synthase binding protein, belongs to the PCH family of proteins, exposing a typical domain structure. While its SH3 domain and the C-terminal coiled-coil region cc2 have been studied earlier, the function of the N-terminal half comprising a Cdc15 domain with an FCH (Fes/CIP homology) region followed by a coiled-coil stretch cc1 is unknown. Here, we show that the FCH region is necessary and sufficient for membrane association of NOSTRIN, whereas the Cdc15 domain further specifies subcellular dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The membrane tubulation by the Rgd1p F-BAR domain in HeLa cells resembles that seen for most mammalian F-BAR domains, including those from FBP17, CIP4, FCHo1/2, pacsin 1, nostrin, and PSTPIP1/2 (Henne et al, 2010; Icking et al, 2006; Itoh and De Camilli, 2006; Itoh et al, 2005; Tsujita et al, 2006), which all bind relatively non-specifically to anionic phospholipids. The FBP17, CIP4, and pacsin 1 F-BAR domains preferentially bind PtdSer-containing membranes, and phosphoinositides typically further enhance membrane binding (Henne et al, 2010; Itoh et al, 2005; Tsujita et al, 2006).…”
Section: Resultsmentioning
confidence: 68%
“…The membrane tubulation by the Rgd1p F-BAR domain in HeLa cells resembles that seen for most mammalian F-BAR domains, including those from FBP17, CIP4, FCHo1/2, pacsin 1, nostrin, and PSTPIP1/2 (Henne et al, 2010; Icking et al, 2006; Itoh and De Camilli, 2006; Itoh et al, 2005; Tsujita et al, 2006), which all bind relatively non-specifically to anionic phospholipids. The FBP17, CIP4, and pacsin 1 F-BAR domains preferentially bind PtdSer-containing membranes, and phosphoinositides typically further enhance membrane binding (Henne et al, 2010; Itoh et al, 2005; Tsujita et al, 2006).…”
Section: Resultsmentioning
confidence: 68%
“…NOSTRIN, a 58kDa protein with high expression in the endothelium [69, 70], has a C terminal coiled-coil motif that may trimerize and serve as a platform for binding of several proteins [71]. Because NOSTRIN also associates with caveolin-1, it is believed that NOSTRIN-dependent movement of eNOS proceeds through a specialized endocytosis of caveolar endosomes [70].…”
Section: Regulation Of No Production: the Dynamic Modulation Of Enosmentioning
confidence: 99%
“…WRP and the srGAP family members have a conserved N-terminal Fes and CIP4 homology BAR-like (F-BAR) domain (Itoh et al, 2005; Aspenström, 2009). Several studies have shown this to be a lipid-binding domain that induces membrane invagination and regulates processes such as endocytosis (Takei et al, 1999; Kamioka et al, 2004; Itoh et al, 2005; Icking et al, 2006; Tsujita et al, 2006; Shimada et al, 2007). Surprisingly, a recent study of srGAP2 showed that its F-BAR domain enhances outward membrane protrusions (Guerrier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%